Crediting Mechanisms Overview - Partnership for Market Readiness (World Bank, Washington, DC, 2015)
This document provides a summary assessment of (presented) scaled-up crediting instruments as well as existing project-based crediting schemes against a number of important general characteristics of such instruments. Its purpose is to provide insights that may inform the design and use of possible scaled-up crediting instruments. This summary assessment begins with an examination of proposals for scaled-up crediting mechanisms. It considers existing crediting instruments, that is, (i) Kyoto project mechanisms (clean development mechanism (CDM) and joint implementation (JI)); and (ii) voluntary emission reductions (VER) schemes (in the non-compliance and voluntary markets). The characteristics (or issues) covered are: (i) national and international circumstances for market-based mechanisms and how these interact; (ii) coverage and boundary setting; (iii) participation and incentives for participation; (iv) caps, baselines, and allocations (or issuance); (v) market integrity and credibility; (vi) monitoring, reporting, and verification (MRV); (vii) program authority and administration; and (viii) potential scaling up modalities.